(untitled) (AOQU (Achilles Orlando Quixote Ulysses). Journal on Epic, 2024)
This contribution aims to analyze the painting A Reading from Homer by Lawrence Alma-Tadema (1885, Philadelphia Museum of Art). It focuses on the iconographic innovation that reworks the 19th-century theme of the relationship between Homer and his audience in relation to the reception of Greek culture and the Homeric question in Victorian England from a gender perspective. The article reconstructs the events linked to the realization of the painting and its sources, focusing on the individual characters that make up the audience listening to the reading from Homer. In particular, it examines the role of the girl at the center of the painting. What female perspective on the epic and Homer was conceived in Victorian England, and what interpretation of that context does Alma-Tadema propose with his painting? Furthermore, the contribution addresses issues pertaining to the evolution of art and taste during the latter half of the nineteenth century. It examines the transformation of the history painting and its integra-tion with the genre painting, the theme of female reading and reading aloud, and the ambivalence evident in Alma-Tadema’s portrayal of the female universe and its representation.